THE APPLICATION OF LAMP DRYER ON PRODUCTION OF MORINGA (MORINGA OLEIFERA) LEAF FLOUR - Triana Lindriati; Maria Belgis; Annisafitri (Jurnal Pangan dan Agroindustri, 2022)
The ultilization of moringa leaf can increase by flour processing where drying is the main step. This research was conducted to determine the physical and chemical characteristics of moringa leaf powder produced by lamp drying compared to solar and ovens dryers. Five variations of drying methods were applied (sunlight, oven 40ºC and 60ºC, lamp dryer 40ºC and 60ºC). The results showed, the lamp dryer produced moringa leaf flour that have good physical and chemical properties, that are yield 35.21 – 35.10%; the highest green degree 4.60 – 4.70; the bulk angle 8.09 – 8.44 and the bulk density 0.43 – 0.43. The water content fulfill the SNI standard, that is :10.03 – 10.13%. Meanwhile, the levels of vitamin C 26.48 – 28.28%; chlorophyll 18.41 – 19.25 mg/L and antioxidant activity 43.45 – 43.84 % of DDPH inhibition. However, the total polyphenol content of moringa leaf flour obtained from lamp drying was the lowest, that is 4.88 – 4.98 mg/L.